До питання виконання многоваріантних розрахунків на міцність на прикладі карабінів - Куценко, Сергій Володимирович; Васильєв, Антон Юрійович; Мухін, Дмитро Сергійович (НТУ "ХПІ", 2017)
У роботі проводиться серія розрахунків напружено-деформованого стану конструкції методом скінченних елементів. Метою цих розрахунків є аналіз впливу низки геометричних параметрів на напружено-деформований стан. Даний аналіз проводиться для пошуку раціональних меж проектних параметрів з точки зору міцності. Серія розрахунків включає в себе поодиноке варіювання одним з параметрів. Об'єктом дослідження виступає сталевий туристичний карабін у формі трапеції. На завершення статті проводиться аналіз отриманих даних.

In this work, a series of calculations of structure stress-strain state by the finite element method is conducted. The objective of these calculations is to analyze the influence of some geometrical parameters on stress-strain state. This analysis is performed to find the boundaries of rational design parameters in terms of strength. Calculations series includes a single variation of one parameter. The object of research is steel tourist carbine of trape-zoidal shape. This object has five main parameters: the length of longitudinal portion of the carbine, the sectional diameter, the height, the radius of the arc bending and longitudinal section. Each parameter varies 4-5 times in range 0.5 to 1.5 from baseline value. For each of parameters static strength calculations were performed. The results are displayed in graphs and tabulated. The influence of each parameter was analyzed. For each parameter recommendations were issued for practical application. Finally, the paper presents conclusions and specifies ways for further research. The path is represented for further automation of calculation process for simplification and more detailed analysis of some aspects of design parameters.
To a question of multivariant calculations of the strength on the example of carabiners
Keywords: метод скінченних елементів; напружено-деформований стан; параметричний аналіз; альпінізм; елементи страховки; індивідуальне спорядження; finite element method; stress-strain state; parametric analysis